Exploration to find green building materials from recycled solid wastes - Din, Abdul Talib; Mohd Hafiz, Norzawahir; Mohd Rus, Anika Zafiah (Penerbit Akademia Baru, 2018)
This research studied the properties and the production of thermal insulation materials from recycled solid waste and their applications in residential house construction. Recycled materials that were used as specimens are aluminum, plastic, bagasse, textile, oil palm leaves, twigs, paper, corn cob, rubber, coconut husk, coconut shell, granite, wood, iron, glass, kenaf, and concrete. The specimens were produced by using composite method with epoxy solution as the binder to the loose grain of recycle waste material. Experimental method of the specimens has also been discussed in this project which is by recording the temperature of each specimen in several time periods and apply the data in the Fourier’s equation to determine heat transfer rate. This project therefore discussed mainly about theory of heat transfer which consist of conduction and radiation. From the research, it is found that textile, oil palm leaves, kenaf, coconut shell, twigs, paper, and coconut fiber are good insulator. Since the quantity of oil palm leaves and textile are abundantly available and have longer life span as compared to the rest, the oil palm leaves and textile are selected to be the based materials for the building insulation.